Vasculopathy, Immunodeficiency, and Bone Marrow Failure: The Intriguing Syndrome Caused by Deficiency of Adenosine Deaminase 2 - Lee, Pui Y. (Frontiers in Pediatrics, 2018)
Deficiency of adenosine deaminase 2 (DADA2) is a monogenic form of systemic vasculopathy that often presents during early childhood. Linked to biallelic mutations in ADA2 (previously CECR1), DADA2 was initially described as a syndrome of recurrent fever, livedo racemosa, early-onset strokes, and peripheral vasculopathy that resembles polyarteritis nodosum. However, the wide spectrum of clinical findings and heterogeneity of disease, even among family members with identical mutations, is increasingly recognized. Evidence of systemic inflammation and vasculopathy is not uniformly present in DADA2 patients and some can remain asymptomatic through adulthood. Humoral immunodeficiency characterized by low immunoglobulin levels and increased risk of infection is another common feature of DADA2. Variable cytopenias including pure red cell aplasia that mimics Diamond-Blackfan anemia can also be primary manifestations of DADA2. How defects in a single gene translate into these heterogeneous presentations remains to be answered. In this review, we will summarize lessons learned from the pleiotropic clinical manifestations of DADA2.